KUALITAS BAKTERIOLOGI PADA DEPOT AIR MINUM ISI ULANG DI KOTA PONTIANAK TAHUN 2007 - -, Suharno; Nasip, Muhammad; Iskandar, Dodi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Based on the datas of health departement of Pontianak City, the Number of the refill drink water storehouse had been achieved 57. People as consumer of it have the right to get insurance of health and safety. Therefore there was needed to study bacte-riolgical test.This study was to get datas and to learn the coliform bacteriological contents of raw water and processed water on the refill drink water storehouse in Pontianak City. Raw water resource in Pontianak was 100 % derived from mountains. It covered 77.2 % of Anjungan, 12.3 % of Paniraman, 10.0 % of Sui Purun. It had Most Probable Coliform Number and Echericia Coli Number were 71.9 % and 59.6 % in sequence. These did not fulfill the requirements of health standard yet. Like wise, processed water of storehouse in Pontianak possessed 33.3 % of Most Probable Coliform Number and 15.4 % of E.Coli Number. The quality of raw water had significant coherence with Most Probable Coliform Number and Echericia Coli Number. Other factors that related to product of processed water quality were: The protection of raw water, disinfection processing, and water re-filling processing to plastic flask. Hence, the advice for processing manager of drinking water were to more taking a care the quality by disinfection pretreatment and protection. It was suggested for the health department to monitor and to evaluate continuesly at least every six months. It was recommended to people to choose selectively became customer of refill drinking water storehousers. Choose between them that had steril and saniter processing.